Peer effects, risk pooling, and status seeking: What explains gift spending escalation in rural China? - Chen, Xi; Kanbur, Ravi; Zhang, Xiaobo (International Food Policy Research Institute, 2011)
It has been widely documented that the poor spend a significant proportion of their income on gifts even at the expense of basic consumption. We test three competing explanations of this phenomenon—peer effect, status concern, and risk pooling—based on a census-type primary household survey in three natural villages in rural China and on detailed household records of gifts received on major occasions. We show that gift-giving behavior is largely influenced by peers in reference groups. Status concern is another key motive for keeping up with the Joneses in extending gifts. In particular, poor families with sons spend more on gift giving in proportion to their income than their rich counterparts, in response to the tightening marriage market. In contrast, risk pooling does not seem to be a key driver of the observed gift-giving patterns. However, we show that large windfall income triggers the escalation of competitive gift-giving behavior.